Teacher Concepts Related to the 4C Based PAI Learning Model at SMPIT Al Haraki Depok - Mundiatul Mila; Armai Arief; Siti Khadijah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Islamic Religious Education in the 21st century faces the challenge of not only transmitting normative knowledge, but also developing critical thinking, creativity, collaboration, and communication (4C) skills in a meaningful way. This article is part of the discourse on religious education and pedagogy in the 21st century, with the aim of conducting an in-depth study of teachers' concepts related to the 4C-based PAI learning model at SMPIT Al Haraki Depok. This study uses a qualitative approach with a case study design. Data were collected through classroom observations, in-depth interviews with the principal, curriculum assistant, and PAI teachers, as well as analysis of learning documentation. This study does not formulate quantitative hypotheses but focuses on the meaning and interpretation of teachers' concepts. The results show that PAI learning has integrated the 4C elements through strategies such as question prompts, information exploration, case studies, discussions, projects, presentations, cross-subject learning, and Student Led Conferences. These practices reflect the social constructivism approach and information theory, in which students play an active role as meaning builders and learning communicators. This article contributes to the development of religious education studies by showing that PAI can be a space for dialogical, collaborative, and reflective learning. These findings emphasize the importance of systematic teacher-based PAI learning design to meet the demands of 21st-century education